Expression of Tim-3 in gastric cancer tissue and its relationship with prognosis - Cheng, Gui (Int J Clin Exp Pathol, 2015)
As a negative regulatory molecule, T-cell immunoglobulin–and mucin domain-3 (Tim-3) plays a crucial role in the tumor immunological tolerance. In the present study, we aimed to determine the Tim-3 expression in gastric cancer tissue and its relationship with clinicopathological parameters and prognosis. The Tim-3 expression was assessed in 52 gastric cancer specimens and 15 gastritis tissues by flow cytometry, and gastritis tissues served as the control. As a result, we found that the Tim-3 expressions on CD4(+)T cells and CD8(+)T cells in gastric cancer tissue was significantly higher than those in gastritis tissue (P=0.022, P=0.047, respectively). The median expression level of Tim-3 on CD4(+)T cells were significantly correlated with clinicopathological parameters, such as tumor size, lymph node metastasis, the depth of tumor invasion and TNM staging (P=0.042, P=0.026, P=0.001, P=0.003, respectively), while it was not correlated with sex, age and histological subtype (all P>0.05). In CD8(+)T cells, the Tim-3 expression was relevant to tumor invasion and TNM staging (P=0.035, P=0.017, respectively), while it was irrelevant to other clinicopathological parameters (all P>0.05). Additionally, Kaplan-Meier survival curves showed that the median overall survival time of patients with lower Tim-3 expression was greater than that of patients with higher Tim-3 expression in CD4(+)T cells and CD8(+)T cells (χ(2)=18.036, P<0.001 and χ(2)=18.036, P<0.001, respectively). Moreover, the multivariate analysis revealed that the Tim-3 expression and TNM stage were independent prognostic factors for gastric cancer patients (P=0.029, P=0.043 and P=0.003, respectively). These results suggest that Tim-3 played an important role in the development and progression of gastric cancer, and it could be used as an independent prognostic factor for gastric cancer patients.